2013
DOI: 10.1055/s-0032-1331841
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Surgery in Dialysis-Dependent Patients: Impact of Gender on Early Outcome in Single-Center Experience with 204 Consecutive Cases

Abstract: Multivariate analysis identified preoperative myocardial infarction, prolonged extracorporeal circulation time, operation time, and surgical reexploration as independent predictors of 30-day mortality. There was a higher occurrence of bleeding complications in men that remained significant even after correction for body surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Renal insufficiency generally seems to have a stronger impact on women than on men. The investigation by Deutsch et al [ 26 ] evaluated the gender influence in dialysis-dependent patients undergoing cardiac surgery. The authors retrospectively reviewed the data of 204 dialysis-dependent patients (68.6% male, age 66.6 ± 9.9 years) with end-stage renal disease undergoing cardiac surgery and compared them to propensity-score-pair-matched controls, also consisting of 204 patients.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal insufficiency generally seems to have a stronger impact on women than on men. The investigation by Deutsch et al [ 26 ] evaluated the gender influence in dialysis-dependent patients undergoing cardiac surgery. The authors retrospectively reviewed the data of 204 dialysis-dependent patients (68.6% male, age 66.6 ± 9.9 years) with end-stage renal disease undergoing cardiac surgery and compared them to propensity-score-pair-matched controls, also consisting of 204 patients.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Multivariate analysis identified preoperative MI, prolonged extracorporeal circulation time, operation time, and surgical reexploration as independent predictors of 30-day mortality. There was a higher occurrence of bleeding complications in men that remained significant even after correction for body surface area [ 26 ].…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…These stark differences in short-term outcomes following cardiac surgical procedures become even more apparent with combined coronary artery bypass grafting plus valve surgeries (2.1-fold increase in mortality and a 1.7-1.8-fold increase in combined morbidity and mortality) [1]. A number of prospective and retrospective studies have shown consistent short-and long-term outcomes in this patient population, with 13-25% 30-day mortality [5][6][7][8], 18-19% 1-year mortality, 59-83% 5-year mortality, and an 81% 10-year mortality (median survival 4.3 years) [7,9]. This patient population also frequently requires complicated cardiac and aortic surgical procedures, and these more complex surgical procedures are also associated with higher shortand long-term morbidity and mortality compared to patients not on dialysis [10][11][12].…”
mentioning
confidence: 95%